A note on the signature representations of the symmetric groups - Lim, Kay Jin (2022)
For a partition λ and a prime p, we prove a necessary and sufficient condition for there to exist a composition δ such that δ can be obtained from λ after rearrangement and no partial sums of δ are divisible by p. To demonstrate why we are interested in the question, we compute some signed p-Kostka numbers.